Analysis of Existentialist Philosophy in The Merdeka Curriculum - Cantika, Varary Mechwafanitiara; Lestari, Risti Dwi; Sapitri, Lenny; Kailani, Rizal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Existentialism philosophy relates to the concept of Merdeka learning contained in the Merdeka curriculum. Understanding in this philosophical school emphasizes the freedom of individual humans in making choices and being responsible for their choices. This understanding aligns with the concept of Merdeka learning, which emphasizes the freedom of students to develop their potential and talents. This study aims to describe the analysis of existentialism philosophy in the Merdeka curriculum. The method used is a literature review with a qualitative approach. The data sources used come from books and research journal articles relevant to the topics raised in this study, namely existentialism, curriculum, learning, and education. The study results show that the concept of Merdeka learning initiated by Ki Hadjar Dewantara strongly connects with the philosophy of existentialism. Freedom to learn and existentialism aim to form an individual with complete freedom. In terms of the planning, implementation, and assessment aspects of the Merdeka curriculum, it can be seen that the concept of Merdeka learning encourages an understanding of the ability and speed of each student to find the truth and learn something while remaining responsible for what they have chosen.